Respuesta :
Step-by-step explanation:
a) 3x + 5y = 8
4x - 3y = 1
• using the elimination method:
3x + 5y = 8 (×4)
4x -3y = 1 (×3)
12x + 20y = 32
12x -9y = 3
subract 12x from both equation:
20y - - 9y= 32 -3
20y +9y = 29
29y= 29
y= 29/29
y= 1
- substituting y= 1 in :
4x - 3y= 1
4x - 3(1) = 1
4x -3 = 1
4x = 1 + 3
x = 4/4
x= 1
b) 6p+ 4q = 20
5p - 2q = 6
• using the elimination method:
6p + 4q = 20
5p - 2q = 6 (×2)
6p + 4q = 20
10p - 4q = 12
add 4q + -4q to eliminate q.
6p+ 10p = 20+12
16p = 32
p = 32/ 16
p = 2
- subtituting p = 2 in :
5p - 2q = 6
5(2) -2q =6
10 -2q = 6
-2q = 6 - 10
q = -4 / -2
q = 2
hope this helps you,
-s.
Answer:
a. x = 1 / y = 1
b. p = 2 / q = 2
Step-by-step explanation:
a.
3x + 5y = 8 ________( 1 )
4x - 3y = 1________ ( 2 )
( 1 ) × 3 ____ 9x + 15y = 24 _____ ( 3 )
( 2 ) × 5____ 20x - 15y = 5 _____ ( 4 )
( 3 ) + ( 4 )
[tex]9x + 15y + 20x - 15y = 24 + 5 \\ 9x + 20x + 15y - 15y = 29 \\ 29x = 29 \\ x = \frac{29}{29} \\ x = 1 \\ [/tex]
x = 1 substitute to ( 1 ) ,
[tex]3x + 5y = 8 \\ 3(1) + 5y = 8 \\ 3 + 5y = 8 \\ 5y = 8 - 3 \\ 5y = 5 \\ y = \frac{5}{5} \\ x = 1 \\ [/tex]
b.
6p + 4q = 20_______ ( 1 )
5p – 2q = 6 _______ ( 2 )
( 2 ) × 2 ____ 10p - 4q = 12 _______ ( 3 )
( 1 ) + ( 3 )
[tex]6p + 4q + 10p - 4q = 20 + 12 \\ 6p + 10p + 4q - 4q = 32 \\ 16p = 32 \\ p = \frac{32}{16} \\ p = 2 \\ [/tex]
p = 2 substitute to ( 1 ) ,
[tex]6p + 4q = 20 \\ 6(2) + 4q = 20 \\ 12 + 4q = 20 \\ 4q = 20 - 12 \\ 4q = 8 \\ q = \frac{8}{4} \\ q = 2 \\ [/tex]